PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR ISLAM TERPADU MUHAMMADIYAH JUMAPOLO KARANGANYAR - Waston Waston; Taryanto Taryanto (Profetika: Jurnal Studi Islam, 2019)
: The way in improving the quality of education institution or a school is determined by the headmaster leadership in an effective management. The progress of school retreat is inseparable from the role of the principal, because the principal acts as a central force which is the driving force of school life. In order for schools to be able to compete, the principal must be committed to change by carrying out his role as the principal. The totality of the role of the principal must have a vision of the future and be able to actualize all existing potential into a synergistic force in order to achieve educational goals. The research objective is to describe the role of the principal in improving the quality of education in SDIT Muhammadiyah Jumapolo Karanganyar 2018/2019 academic year. This type of research is in the form of field research with qualitative descriptive analysis, and uses a sociological approach. Methods of collecting data through interviews, observation, and documentation. The results of this study indicate that, First, the role of principals in improving the quality of education in SDIT Muhmamadiyah Jumapolo is realized by: 1) Increasing teacher professionalism, 2) Improving the quality of learning, 3) Improving facilities and infrastructure, 4) Increasing student learning motivation. Second, the principal's strategy in improving the quality of education at SDIT Muhmamadiyah Jumapolo is done by: 1) Increasing teacher professionalism carried out with the OJT period (On Job Training) for new teachers and self-development for old teachers and intensive motivational development, 2) Improving the quality of learning done by integrating four curricula (DIKNAS, KEMENAG, PONPES GONTOR and ISMUBA) with a variety of learning methods approach 3) Improvement of facilities and infrastructure carried out by optimizing the utilization of existing SARPRAS and procurement of SARPRAS needed, 4) Increasing motivation for student learning by giving reward and punishman, giving praise and competition.The key word: visionary leadership, headmaster, quality of education. Third, the obstacles and solutions to the role of principals in improving the quality of education at SDIT Muhmamadiyah Jumapolo include: 1) Increasing teacher professionalism such as teacher recruitment that is not suitable for qualifications. The solution is to participate in self-development activities and re-study or further study, 2) Improving the quality of learning such as school status that is not ful day school. The solution is by organizing material and reducing material in the gontor curriculum, 3) Improving facilities and infrastructure such as funding problems. The solution is cooperation with student guardians and donors, 4) Increased learning motivation of students such as children lacking assistance at home. The solution is intense collaboration and communication between the teacher and parents of children through via cell phones, contact books and home visits.Abstrak: Upaya memperbaiki kualitas dalam suatu lembaga pendidikan atau sekolah sangat ditentukan oleh kepemimpinan kepala sekolah dalam manajemen yang efektif. Maju mundurnya sekolah tidak terlepas dari peran kepala sekolah, karena kepala sekolah berperan sebagai kekuatan sentral yang menjadi kekuatan penggerak kehidupan sekolah. Agar sekolah mampu bersaing, kepala sekolah harus memiliki komitmen dalam perubahan dengan menjalankan perannya sebagai kepala sekolah. Totalitas peran kepala sekolah harus mempunyai visi masa depan serta mampu mengaktualisasikan seluruh potensi yang ada menjadi sesuatu kekuatan yang bersinergi guna mencapai tujuan pendidikan. Tujuan penelitian adalah mendiskripsikan peran kepala sekolah dalam meningkatkan mutu pendidikan di SDIT Muhammadiyah Jumapolo Karanganyar tahun pelajaran 2018/2019. Jenis penelitian ini berupa penelitian lapangan dengan analisis deskriptif kualitatif, dan memakai pendekatan sosiologis. Metode pengumpulan data dengan wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa, Pertama, peran kepala sekolah dalam meningkatkan mutu pendidikan di SDIT Muhmamadiyah Jumapolo diwujudkan dengan: 1)Peningkatan profesionalisme guru, 2)Peningkatan kualitas pembelajaran, 3)Peningkatan sarana dan prasarana, 4)Peningkatan motifasi belajar siswa. Kedua, strategi kepala sekolah dalam meningkatkan mutu pendidikan di SDIT Muhmamadiyah Jumapolo dilakukan dengan: 1)Peningkatan profesionalisme guru dilakukan dengan masa OJT (On Job Training) bagi guru baru dan pengembangan diri bagi guru lama serta pembinaan motivasi secara intensif, 2)Peningkatan kualitas pembelajaran dilakukan dengan mengintegrasikan empat kurikulum (DIKNAS, KEMENAG, PONPES GONTOR dan ISMUBA) dengan pendekatan berbagai metode pembelajaran 3)Peningkatan sarana dan prasarana dilakukan dengan cara optimalisasi pemanfaatan SARPRAS yang ada dan pengadaan SARPRAS yang dibutuhkan, 4)Peningkatan motifasi belajar siswa dilakukan dengan cara pemberian reward dan punishman, pemberian pujian dan kompetisi. Ketiga, kendala dan solusi peran kepala sekolah dalam meningkatkan mutu pendidikan di SDIT Muhmamadiyah Jumapolo diantaranya: 1)Peningkatan profesionalisme guru seperti rekruetmen guru yang tidak sesuai kualifikasi. Solusinya adalah dengan menguikutsertakan dalam kegiatan pengembangan diri dan studi ulang atau study lanjut, 2)Peningkatan kualitas pembelajaran seperti status sekolah yang bukan ful day school. Solusinya dengan pengorganisasian materi dan pengurangan materi di kurikulum gontor, 3)Peningkatan sarana dan prasarana seperti masalah pendanaan. Solusinya adalah kerja sama dengan wali murid dan pendonatur, 4)Peningkatan motifasi belajar siswa seperti anak kurang pendampingan di rumah. Solusinya adalah kerja sama dan komunikasi intens antara guru dan orang tua anak melalui via HP, buku penghubung dan home visit.